2021
DOI: 10.3390/children8100932
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relation between Atopic Diseases and Lifestyle Patterns among Adolescents Living in Greece: Evidence from the Greek Global Asthma Network (GAN) Cross-Sectional Study

Abstract: Introduction: Diet and physical activity might be associated with the risk of allergic diseases in childhood. However, evidence in literature is sparse and diverse. We aim to examine the associations between four healthy dietary consumption pattern drinks, plus the adherence to a physically active lifestyle with atopic diseases (asthma, allergic rhinitis and eczema) in adolescence and their relative importance. Methods: A total of 1934 adolescents (921 boys, 47.5%) and their parents completed a validated quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Table S3 shows the baseline characteristics of the cohort and cross-sectional studies recorded separately in this meta-analysis, while Table S4 presents the specific statistical values in each article. In total, 63 articles were included for data analysis, due to the inclusion of the same population in the four articles by Arvaniti et al 57 , 58 and Antonogeorgos et al 86 , 87 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table S3 shows the baseline characteristics of the cohort and cross-sectional studies recorded separately in this meta-analysis, while Table S4 presents the specific statistical values in each article. In total, 63 articles were included for data analysis, due to the inclusion of the same population in the four articles by Arvaniti et al 57 , 58 and Antonogeorgos et al 86 , 87 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 articles included, 8 33 , 34 , 59–62 , 69 , 81 were cohort studies and 55 22 , 27–32 , 35–57 , 63–68 , 70–80 , 82–86 , 88–90 were cross-sectional studies. Regarding the geographical area, one article 83 originated from Africa, one article 51 was international, 13 articles 30–32 , 35 , 36 , 41 , 47 , 64 , 73 , 74 , 76 , 77 , 80 were published in Asia, 27 articles 22 , 27 , 29 , 33 , 34 , 37–39 , 43–46 , 48 , 49 , 55–57 , 59 , 62 , 69 , 70 , 72 , 81 , 82 , 86 , 88 , 90 originated from Europe, 7 articles 50 , 53 , 54 , 63 , 68 , 84 , 89 from North America, 4 articles 28 , 40 , 60 , 61 from Oceania and 10 articles 42 , 52 , 65–67 , 71 , 75 , 78 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 However, the GAN study for Greece reported an inverse relationship between an active lifestyle and rhinoconjunctivitis. 43 Moreover, a number of studies also investigated the association between cat exposure and atopic disease. Results, however, are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…11 The Greek part of the GAN study included adolescents aged 13-14 years and followed the same protocol of the study. 12…”
Section: Designmentioning
confidence: 99%